Management of mental health policy in daily life: contributions from the Santos network analysis - de Jesus Ligeiro Braga, Fernanda; Togni de Lima e Silva Surjus, Luciana (Brazilian Journal of Mental Health, 2022)
It is understood that the management of a policy plays a key role in its effectiveness, given that it is responsible for its direction, monitoring and evaluation of results. The aim was to understand how the mental health policy is developed in everyday life, identifying strengths and challenges from the perspective of service managers, mental health coordination and workers in the city of Santos/SP. Qualitative research was carried out based on field diary records of three meetings of a Mental Health Workers Forum; a focus group with 10 members of a Management Collegiate; and a semi-structured interview with a member of the mental health coordination. It was observed that there are challenges arising from the construction of team work, intra and intersectorial networking, and the precariousness of the services. The relationship with the local universities enables the integration of students in the services, contributing to the tensioning of issues pertinent to the field and to the continuing education of the workers. As a way of strengthening the policy and aiming at a more participative management, the Collegiate and Forum spaces were pointed out, but their discussions and actions are deprived from their cogestive function, since they are not translated into concrete changes. It can be noticed that there is a certain invisibility of the contribution of the management work in sustaining the antimanicomial model of care. The role of the managers includes administrative and technical functions, formulation and implementation of the policy.